ACTIVE INTERACTION AS LECTURERS’ STRATEGIES TO PROMOTE SPEAKING CLASSROOM - Ririn Putri Ananda; Patri Dinkuswari (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The goal of this study is to understand the strategies of lecturers and the dominant strategies of lecturers used by lecturers. This research discussed about the promotion of active participation in speaking classrooms by lecturers. This research employed qualitative design for analysis.The instrument were a questionnaire focused on (Jia,2013) theory and an interview. The results demonstrated that the lecturers completely used all strategies namely, improving questioning strategies, attending to learners' linguistic level, implementing cooperative learning, building positive teacher-learner rapports, reducing classroom anxiety. From those strategies, The highest percentage of strategies implementation leads to attending to learners' linguistic level. The result implies that it is necessary to introduce the use of strategies to encourage active classroom to develop the comprehension of the students and to establish an efficient way to teach speaking.Â Keywords: Strategies, Teaching Srategy, Speaking.